Effect of Cereal Grains on the Total Lipid, Cholesterol Content and Fatty Acid Composition of Liver and Muscle Tissues in Native Geese - Kalayci, Serpil; Yilmaz, Okkes (Kafkas Univ, Veteriner Fakultesi Dergisi, 2014)
In this study we evaluated the effect of cereal grains on total lipid, cholesterol content and fatty acid composition of liver and muscle tissues in native geese. The thirty five geese used in the study were divided into five groups of seven. The groups of geese feed with barley, wheat, rye and corn, respectively. The first group was used as the control group. Water and feed were provided for ad libitum consumption for 6 weeks. While the level of total cholesterol in the liver tissue decreased (P<0.001) in barley and wheat groups, it of the thigh muscle decreased (P<0.001) in all groups. While the total lipid content of the liver tissue increased in rye and corn groups (P<0.001), it of the thigh muscle increased (P<0.001) in wheat and rye groups. While the total lipid content of the back muscle decreased in barley and wheat groups (P<0.001), it of the breast muscle decreased (P<0.001) in wheat, rye and corn groups. Although the amount of palmitic acid in the liver tissue increased (P<0.001) in the rye group, the amount of stearic decreased (P<0.001) in the barley group. The amount of arachidonic, docosahexaenoic, PUFA, n-3 and n-6 acids in the liver tissue increased (P<0.001) in the wheat, rye and corn groups. Consequently, in addition to other foods, rye could be used as a valuable nutrition of the geese diet.
Yerli kazlarda karaci?er ve kas dokulari{dotless}ni{dotless}n total lipit, kolesterol i?çeri?i ve ya? asidi kompozisyonu üzerine tahi{dotless}l tanelerinin etkisi
Keywords: Cereal Grains; Cholesterol; Total lipid; Liver; Muscle; Geese Diet